The Impact of Precipitation Characteristics on the Washout of Pollutants Based on the Example of an Urban Catchment in Kielce - Bartosz Szeląg (MDPI AG, 2021)
This paper reports the results of studies on the concentrations of total suspended solids (TSS) and heavy metals (HMs) (Cu, Zn, Cr, Ni, Cd, Pb) in stormwater. Pollutant loads were calculated for the observed high water stages. Pollutographs showing M/Mc = f(V/Vc) relationships were generated. In the description of the relationships, two functions, namely the exponential and the power functions, were employed. These represented the dynamics of the pollutant washout from the surface of the catchment area. The analyses demonstrated that the exponential function provides a slightly better description of the course of the process compared with the power function. In the former case, correlation coefficients (R) ranged from 0.900 to 0.999, whereas in the latter they ranged from 0.864 to 0.999. The analyses of correlations between the characteristics describing discharge hydrographs and the values of pollutant washout coefficients indicate that the strongest statistical relationships were identified for TSS. It was demonstrated that the value of the washout coefficient for total suspended solids (kTSS) drops with an increase in rain intensity (q). This also depends on the 10-min precipitation (Ptd=10). Regarding the studied heavy metals, a statistically significant impact of the dry period (tbd) on the washout coefficient was observed only for lead (kPb). Taking into account the washout coefficient in the first flush model makes it possible to improve the accuracy of calculations. This is important for understanding the studied phenomenon.